Effects of monetary policy in a model with cash-in-advance constraints on R&D and capital accumulation - Daiki Maeda; Yuki Saito (Osaka University, Institute of Social and Economic Research (ISER), 2020)
To examine the effect of monetary policy on economic growth, we formulate an endogenous growth model with cash-in-advance constraints on R&D and capital accumulation as endogenous growth engines. Within this framework, we show that the relationship between economic growth and the nominal interest rate can be an inverted-U shape. Moreover, we demonstrate that the welfare-maximizing level of the nominal interest rate is larger than the growth rate-maximizing level of the nominal interest rate.
Keywords: E52; O31; O40; 330; Capital accumulation; CIA constraint; Endogenous growth; Monetary policy; R&D